On the Pulse Extension Loss in Digital Beamforming SAR - Younis, Marwan; Rommel, Tobias; Bordoni, Federica; Krieger, Gerhard; Moreira, Alberto (IEEE Geoscience and Remote Sensing Letters, 2015)
One of the benefits of synthetic aperture radar (SAR) systems utilizing digital beamforming is the ability to increase the receive power. The relevant SAR technique is known as SCan-On-REceive (SCORE), which steers the receive antenna beam such that it follows the radar pulse echo traversing the ground. This allows the use of a narrow receive beam in elevation, and therefore, the height of the receive antenna can be increased, resulting in a higher gain, which explains the higher receive power. Although advantageous, this technique has some pitfalls, which impose an upper limit on the antenna size and constrain the selection of SAR operation parameters. These limitations (which are often neglected in the system conception) are caused by the pulse extent on the ground and the way it is modulated by the receive antenna pattern. This letter addresses and quantifies the effects caused by the transmit pulse length (here denoted as pulse extension loss) through a rigorous analysis, with the purpose of introducing an important SAR performance figure. Closed expressions are derived for the simplified case of a uniform linear antenna array.
DLR Import::2019-04-02
Keywords: Calibration; digital beamforming; pulse extension loss; SAR; SCORE; SNR; SweepSAR